Yield and fruit quality of citrus species relative to foliar sprays of macronutrients - Mudau, N. Fhatuwani (Nixwell Fhatuwani) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2001.